PREDICTION OF THE PROBABILITY OF THE DEVELOPMENT OF THE ONCOLOGICAL PROCESS AS MULTIFOCAL, TAKING INTO ACCOUNT GENETIC AND MOLECULAR MARKERS. CLINICAL CASE - Ніколаєнко-Камишова, Тетяна; Василевська, Ірина (SWorldJournal, 2023)
The incidence of oncological diseases is continuously increasing. The improvement of the situation at the present time involves establishing a diagnosis at the early stages of tumor development. Since malignant transformation at the cellular level leads t